The Influence of Principal’s Leadership and Internal Communication toward Teacher’s Performance of a Driving School - Agustina, Yuli; Ahyani, Nur; Fitria, Happy (Journal of Social Work and Science Education, 2023)
This study aims to determine the influence of principal leadership and internal communication on the performance of driving school teachers in public high schools in the Kayuagung district. This research was conducted at Kayuagung 1 Public High School, Kayuagung 2 Public High School and Kayuagung 3 Public High School. This research uses quantitative methods. The population in this study amounted to 137 people. The sample in this study amounted to 58 people. Data obtained through questionnaires and documentation techniques. To analyze the data, it was carried out through correlation tests, simple linear regression and multiple regression, which had previously been tested for data normality, linearity, multicollinearity and heteroscedasticity as prerequisite tests. The results of the study stated that there was a positive influence on the leadership of the principal and internal communication together on the performance of driving school teachers in public high schools in the Kayuagung district.